FLASHCARD BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN TOLERANSI DAN HASIL BELAJAR PADA MUATAN PENDIDIKAN PANCASILA SEKOLAH DASAR - I Putu Angga Pratama Sapta Widya Putra; I Ketut Gading; I Gede Margunayasa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low levels of students’ tolerance attitudes and learning outcomes in the Pancasila Education subject, particularly in the Aku Anak Indonesia material, as well as the suboptimal use of technology in the learning process. The purpose of this study was to develop an Augmented Reality (AR)-assisted flashcard learning medium and to examine its acceptability, practicality, and effectiveness in improving the tolerance attitudes and learning outcomes of third-grade students at SD Negeri 2 Sinabun. This research employed a development research method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The acceptability test involved two experts, the practicality test involved two teachers and students, while the effectiveness test employed a pretest-posttest control group design analyzed using MANOVA. The results showed that the developed media had a very high level of acceptability, with an average score of 3.91 (very valid). The practicality test results indicated percentages of 97.5% and 95% from teachers and 89% from students, which were categorized as very practical. The effectiveness test revealed that the AR-assisted flashcard media had a significant effect on students’ tolerance attitudes (F = 719.206; p < 0.05) and learning outcomes (F = 69.041; p < 0.05). Simultaneously, the media was also proven effective in improving tolerance attitudes and learning outcomes, with a significance value of 0.000 and a Partial Eta Squared value of 0.957. Therefore, the Augmented Reality-assisted flashcard media was declared valid, practical, and effective for use in teaching the Aku Anak Indonesia topic in Pancasila Education for third-grade elementary school students.